Do mergers enhance financial performance? Empirical evidence from the Czech Republic - Tomáš Podškubka; Lucie Jahodová; Josef Arlt (Financial Internet Quarterly, 2025)
This study investigates whether the post-merger performance of companies in the Czech Republic exceeds their pre-merger performance. Employing the Czech-specific IN05 model and internationally recognized composite financial performance indicators (Altman Z-score, Taffler model, and Kralicek Quick Test), the research utilizes a comprehensive dataset of 1,077 companies involved in mergers. The analysis spans a decade, covering five years before and after the mergers conducted in 2016. Results indicate that while the financial condition of merging companies shows stagnation, successor companies demonstrate statistically significant improvements in key financial indicators, especially during the period from 2017 to 2021. This highlights the positive impact of mergers on financial performance, even amid external disruptions such as the COVID-19 pandemic. These findings contribute to understanding M&A dynamics in medium-sized, open economies within the EU, offering valuable insights for both academic research and practical applications in corporate strategy.
Keywords: D22; D23; G34; 330; Post-Acquisition Performance; Mergers; Synergies; Mixed Effect Model